2010
DOI: 10.2308/accr.2010.85.4.1163
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Executives on Corporate Tax Avoidance

Abstract: This study investigates whether individual top executives have incremental effects on their firms’ tax avoidance that cannot be explained by characteristics of the firm. To identify executive effects on firms’ effective tax rates, we construct a data set that tracks the movement of 908 executives across firms over time. Results indicate that individual executives play a significant role in determining the level of tax avoidance that firms undertake. The economic magnitude of the executive effects on tax avoida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
544
1
77

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 1,197 publications
(657 citation statements)
references
References 30 publications
35
544
1
77
Order By: Relevance
“…Therefore, it may be concluded that remuneration negatively influences the tax management detected by means of the variable BTD. This finding is consistent with the papers by Desai and Dharmapala (2006), Minnick and Noga (2010), Dyreng et al (2010), Rego and Wilson (2010), and Armstrong et al (2011), who identified a significant relationship between remuneration and BTD. Finally, H 6 and H 7 may be proven by the results, demonstrating that remuneration and the previous tax management influence the tax management detected through ETR, CashETR, and BTD, regardless of the fact that the company is classified at specific levels on the BM&FBOVESPA or at the traditional Market, as the control variable (Gc) was significant only in the model in Table 6.…”
Section: Panel Data Model For the Variable Btdsupporting
confidence: 82%
See 4 more Smart Citations
“…Therefore, it may be concluded that remuneration negatively influences the tax management detected by means of the variable BTD. This finding is consistent with the papers by Desai and Dharmapala (2006), Minnick and Noga (2010), Dyreng et al (2010), Rego and Wilson (2010), and Armstrong et al (2011), who identified a significant relationship between remuneration and BTD. Finally, H 6 and H 7 may be proven by the results, demonstrating that remuneration and the previous tax management influence the tax management detected through ETR, CashETR, and BTD, regardless of the fact that the company is classified at specific levels on the BM&FBOVESPA or at the traditional Market, as the control variable (Gc) was significant only in the model in Table 6.…”
Section: Panel Data Model For the Variable Btdsupporting
confidence: 82%
“…Besides, the results shown herein are consistent with the papers by Minnick and Noga (2010), Dyreng et al (2010), and Rego and Wilson (2010), who identified a significant relationship between remuneration and CashETR. In this model, no significant relationship was noticed between corporate governance and the dependent variable.…”
Section: Panel Data Model For the Variable Cashetrsupporting
confidence: 82%
See 3 more Smart Citations